(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2024)
One of the characteristics of the Iron Age cultures in the north of the Iberian Peninsula is the absence of writing at times prior to the Roman conquest. In 2017, the excavations carried out in Peña del Castro (León) resulted in the discovery of a spindle whorl with a sign engraved on its surface. The present work aims to make known this element and its context, which may be an example of an inscription in the Celtiberian alphabet, similar to those found in the Meseta area.